Contraception and Sexsual Activity as Factor Influenced Leucorrhea - Sari Priyanti; Agustin Dwi Syalfina (Universitas Airlangga, 2017)
Cervical cancer is a non-communicable disease that is worrying for the public and causes an increase in mortality in women. One of the earliest signs of cervical cancer is leucorrhoea. The incidence of leucorrhoea in Indonesian women is 90% of which > 75% of women experience leucorrhoea once and another 25% have leucorrhoea ≥ 2 times. The research aims to analyze the factors that influence the incidence of leucorrhoea. This study was an observational analytic study with cross-sectional study design. The population studied was all women of childbearing age who used contraceptives in Karang Jeruk Village, Jatirejo Sub-district, Mojokerto district in March 2017. The sample in this study was 33 people. Data collection using interview techniques with questionnaire guidelines. Data analysis uses logistic regression. The majority of respondents aged 20-35 years (75.8%), had primary-secondary education (45.8%), did not have a job (60.6), and multipara (54.5%). Birth control (PR = 10,000; 95% CI = 1,732-57,722) and sexual activity (PR = 8,750; 95% CI = 1,466-52,232) have a significant effect on the incidence of leucorrhea, so it is advisable to get married and first sexual behavior at the age of ≥ 20 years, limiting the number of children no more than 2 because the more the number of children, the greater the risk of leucorrhoea and not using hormonal contraception for a long period of time, which is more than 2 years.